Political trust and attitudes toward civil disobedience: evidence from Taiwan. Issue 7 (3rd October 2022) - Wang, Ching-Hsing; Lin, Tsong-Jyi; Hsiao, Yi-ching; Chang, Yi-Bin; Weng, Dennis Lu Chung
ABSTRACT: While civil disobedience has been widely studied by political theorists, little scholarly attention has been paid to empirical investigation of civil disobedience. This study represents one of the very few attempts to examine the determinants of individual attitudes toward civil disobedience. This study examines the relationship between political trust and sense of civil disobedience and argues that people with higher levels of political trust exhibit lower levels of civil disobedience because they tend to feel satisfied with the political system and have less incentive to challenge the government. Using two original datasets collected immediately after the Red Shirt Movement in 2006 and the Sunflower Movement in 2014 in Taiwan, this study consistently finds a negative relationship between political trust and individual attitudes toward civil disobedience, implying that political trust plays an important role in decreasing individual motivation to disobey the laws or the government. Besides, this study finds that people supporting the opposition camp have higher levels of civil disobedience, whereas those supporting the incumbent's camp display lower levels of civil disobedience. This suggests that an individual's level of civil disobedience depends on which party is in power. Overall, this study provides new insights into the basis for civil disobedience.